UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PKn DENGAN METODE ˜TATAS™ PADA SISWA KELAS VIII-3 SMP NEGERI 2 MUARA TAHUN PELAJARAN 2019/2020 - Hutabarat, Enda (JGK (Jurnal Guru Kita), 2020)
Abstract: Efforts to Improve Motivation and Learning Outcomes of Pkn with the 'Tatas' Method in Class Viii-3 Junior High School 2 Muara Students in 2019/2020 Academic Year. The purpose of this classroom action research is to increase the motivation and learning outcomes of Civics class VIII-3 students using the "Tatas" method. This classroom action research was conducted at SMP Negeri 2 Muara. The number of students is 34 students. Based on the results of the analysis showed that the independent learning of students, who stated that they were less independent, decreased from 13 students (40.63%) in the pre-action, to 9 students (28.13) in the first cycle, and to 5 students (15.63%) in cycle II. Independent students experienced an increase from 17 students (53.13%) in the pre-action, to 19 students (59.38%) in the first cycle, and to 18 students (56.25%) in the second cycle. Very independent students experienced an increase from 2 students (6.25%) in the pre-action, to 4 students (12.50%) in the first cycle, and to 9 students (28.13%) in the second cycle. in cycle I and cycle II. Students who showed displeasure there was a decrease from 13 students (40.63%) in the pre-action to 10 students (31.25%) in the first cycle and to 3 students (9.38%) in the second cycle. Students who expressed pleasure experienced an increase from 12 students (37.50%) in the pre-action to 15 students (46.88%) in cycle I, and to 17 students (53.23%) in cycle II. Students who said they were very happy experienced an increase from 2 students (6.25%) in the pre-action to 7 students (21.88%) in the first cycle, and to 12 students (37.50%) in the second cycle. the increase in complete learning from 17 students (53.13%) in the pre-action to 22 students (68.75%) in the first cycle, and to 28 students (87.50%) in the second cycle. Meanwhile, those who have not finished learning have decreased from 15 students (46.88%) in the pre-action to 10 students (31.25%) in the first cycle, and to 4 students (12.50%) in the second cycle. Based on the results of the research analysis as explained above, the action hypothesis states that "if the 'Tatas' method is used in Civics learning the nature of the state material, then the motivation and learning outcomes of class students at SMP Negeri 2 Muara in class VIII-3 students in the 2019/2020 school year will increase. " acceptable. Keywords: Learning Motivation, Civics Lessons, 'Tatas' Method Abstrak: Upaya Meningkatkan Motivasi Dan Hasil Belajar Pkn Dengan Metode ˜Tatas™ Pada Siswa Kelas Viii-3 Smp Negeri 2 Muara Tahun Pelajaran 2019/2020. Tujuan penelitian tindakan kelas ini adalah untuk meningkatkan motivasi  dan hasil belajar PKn siswa kelas VIII-3 dengan menggunakan Metode ˜Tatas™.  Penelitian tindakan kelas ini dilaksanakan di SMP Negeri 2  Muara.  Jumlah siswa ada 34 siswa. Berdasarkan hasil analisis menunjukkan bahwa kemandirian belajar siswa, yang menyatakan kurang mandiri mengalami penurunan dari 13 siswa (40,63%) pada pra tindakan, menjadi 9 siswa (28,13) pada siklus I, dan menjadi 5 siswa (15,63%) pada siklus II.  Siswa mandiri mengalami kenaikan dari 17 siswa (53,13%) pada pra tindakan, menjadi 19 siswa (59,38%) pada siklus I, dan menjadi 18 siswa (56,25%) pada siklus II.  Siswa sangat mandiri mengalami kenaikan dari 2 siswa (6,25%) pada pra tindakan, menjadi 4 siswa (12,50%) pada siklus I, dan menjadi 9  siswa (28,13%) pada siklus II.  pada siklus I dan siklus II.  Siswa yang menunjukkan kurang senang ada penurunan dari 13 siswa (40,63%) pada pra tindakan menjadi 10 siswa (31,25%) pada siklus I dan menjadi 3 siswa (9,38%) pada siklus II. Siswa yang menyatakan senang mengalami kenaikan dari 12 siswa (37,50%) pada pra tindakan menjadi 15 siswa (46,88%) pada siklus I, dan menjadi 17 siswa (53,23%) pada siklus II.  Siswa yang menyatakan sangat senang mengalami kenaikan dari 2 siswa (6,25%) pada pra tindakan menjadi 7 siswa (21,88%) pada siklus I, dan menjadi 12 siswa (37,50%) pada siklus II.  kenaikkan yang tuntas belajar dari 17 siswa (53,13%) pada pra tindakan menjadi 22 siswa (68,75%) pada siklus I, dan menjadi 28 siswa (87,50%) pada siklus II.  Sedangkan yang belum tuntas belajar mengalami penurunan dari 15 siswa (46,88%) pada pra tindakan menjadi 10 siswa (31,25%) pada siklus I, dan menjadi 4 siswa (12,50%) pada siklus II.Berdasarkan hasil analisis penelitian sebagaimana dijelaskan di atas, maka hipotesis tindakan yang menyatakan bahwa œjika metode ˜Tatas™ digunakan dalam pembelajaran PKn materi hakikat negera, maka motivasi dan hasil belajar siswa kelas di SMP Negeri 2  Muara pada siswa kelas VIII-3 pada tahun pelajaran 2019/2020  meningkat dapat diterima. Kata Kunci :  Motivasi Belajar, Pelajaran PKn, Metode ˜Tatas™